2020
DOI: 10.4183/aeb.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin And Isoquercitrin Inhibiting Hepatic Gluconeogenesis Through Lkb1-Ampka Pathway

Abstract: Objective. To observe the impact of quercetin and isoquercitrin on gluconeogenesis in hepatocytes. Methods. Mouse primary hepatocytes were cultured with lactic acid and pyruvic acid. After treatment with quercetin and isoquercitrin for 24 hours, the glucose concentration in the culture supernatant was determined. RT-PCR was used to detect the mRNAs of PEPCK, G6Pase, LKB1, and AMPKα. Protein levels of LKB1, AMPKα, and Thr172 phosphorylation were evaluated by Western blot. Results. The glucose concentration in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Phloridzin has been reported to decrease obesity, insulin resistance, and liver lipid degeneration (Shin et al, 2016). Isoquercitrin and quercitrin prevent liver injury and improve metabolic homeostasis (Chen et al, 2020), which is consistent with the experimental results of this study. Based on the hypoglycemic and hypolipidemic potential of related species in animal models, and the diversified in vitro and in vivo pharmacological properties of EMT, the current experiments were designed to evaluate the anti‐glucose and lipid metabolism effects of M. toringoides leaves in HFruD‐induced mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Phloridzin has been reported to decrease obesity, insulin resistance, and liver lipid degeneration (Shin et al, 2016). Isoquercitrin and quercitrin prevent liver injury and improve metabolic homeostasis (Chen et al, 2020), which is consistent with the experimental results of this study. Based on the hypoglycemic and hypolipidemic potential of related species in animal models, and the diversified in vitro and in vivo pharmacological properties of EMT, the current experiments were designed to evaluate the anti‐glucose and lipid metabolism effects of M. toringoides leaves in HFruD‐induced mice.…”
Section: Discussionsupporting
confidence: 92%
“…When insulin resistance occurs in the body, the pancreatic β cells are required to secrete more insulin to maintain glucose homeostasis, which will lead to hyperglycemia and hyperinsulinemia (Pories & Dohm, 2012). Evidence has shown that in rats fed with 66% fructose, the insulin receptor mRNA and insulin receptor numbers in skeletal muscle and liver were decreased (Chen et al, 2020). In the present study, the Fru group mice showed insulin resistance, which included hyperglycemia, hyperinsulinemia, and high HOMA‐IR.…”
Section: Discussionmentioning
confidence: 99%
“…QUR is a compound that is part of bioflavonoids, a potent antioxidative and anti-inflammatory natural compound found in several vegetables and fruits (Chen et al, 2020;Sharifi-Rad et al, 2020d). Due to its anti-inflammatory effect, some studies have shown that QUR can be useful as a complementary treatment for neurodegenerative diseases such as AD or PD, by stimulating the expression of HO-1, which reduces NO production and suppress pro-inflammatory markers, TNF-α and IL-1α.…”
Section: Discussionmentioning
confidence: 99%
“…This phytochemical and fingerprint information could be considered tools for monitoring the quality of extract and identification purposes. Also, our study identified quercetin as a chemical marker compound with a known antidiabetic activity [ 44 , 45 ]. Accurate identification of this flavonoid compound and its occurrence in appreciable quantity in AEFE further assure potential antidiabetic activity of the AEFE.…”
Section: Discussionmentioning
confidence: 99%